2007
DOI: 10.1515/htmp.2007.26.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Micro Porous Metal Components by Metal Injection Molding Based Powder Space Holder Method

Abstract: A novel production method for the metal components with micro-sized porous structures has been developed by applying the powder space holder (PSH) method to the metal powder injection molding (MIM) process. This production method is compatible with widespread applications with high functionality such as heat sinks, electrodes and medical implants and so on. These applications can benefit from the advantages provided by micro-porous metal components with complicated shapes using most kinds of metal powder. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…However, PMMA, NaCl, and KCl are stable at MIM temperatures. These materials in powder form are usually used as space holders for the manufacturing of porous titanium by MIM . If the salts are applied as a space holder, pores are usually created by dissolution of NaCl or KCl particles in warm water (Figure , route A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PMMA, NaCl, and KCl are stable at MIM temperatures. These materials in powder form are usually used as space holders for the manufacturing of porous titanium by MIM . If the salts are applied as a space holder, pores are usually created by dissolution of NaCl or KCl particles in warm water (Figure , route A).…”
Section: Introductionmentioning
confidence: 99%
“…Nishiyabu et al first demonstrated the potential of MIM for manufacturing net‐shaped parts with functional macropores using a fine‐grained 316L powder and PMMA space holder . Porosity up to 80% was achieved by using a special combination of metal and space holder particles sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporating conditions of the microbeads for successful bulk formation and the formation process of porous microstructure were examined. This sacrificial filler template approach has been called "powder space holding (PSH) method", 33)35) a preexisting powder metallurgical technique's name, by the authors.…”
Section: )13)mentioning
confidence: 99%
“…MIM has gained a solid commercial position as a manufacturing technique for stainless steel parts [24]. The fabrication of porous 316L stainless steel by combining the MIM and PSH methods has been demonstrated by using poly(methyl methacrylate) (PMMA) as a space holder [25][26][27].…”
Section: Introductionmentioning
confidence: 99%